An analysis tool for the installation of submarine cables in an s-lay configuration including "in and out of water" cable segments - Mamatsopoulos, Vasileios A.; Michailides, Constantine; Theotokoglou, Efstathios E. (My University, 2020)
Today, the offshore oil and gas and wind power industry is a heavily regulated segment, and current standards have established restrictions which yield a very limited weather window for submarine cable installations due to experience with cable failure in bad weather. There are two main limiting factors in current practice during cable installation of an S-lay configuration: the design criterion for the minimum allowable radius of curvature in the touch down point and the avoidance of axial compression in the touch down zone. Accurate assessment of the cable integrity during offshore installation has drawn great attention and is related to the existing available analysis and design tools. The main purpose of this paper is to develop and propose a quick and easy custom-made analysis tool, which is able to export similar results as sophisticated finite element analysis software. The developed tool utilizes analytical equations of a catenary-type submarine structure extended to account for varying cross-sections with different weights and/or stiffnesses, as is the real practice. A comparative study is presented in this paper to evaluate the significance for the modeling of the "out of water" cable segment required for accurate safety factor quantification during a laying operation. The eciency and accuracy of the proposed tool are proven through a validation study comparing the results and the computational effort and time with commercial finite element analysis software. The analysis error in the case of not modeling the "out of water" cable part is significant, especially in shallow water areas, which proves the importance of using the proposed analysis tool.
Keywords: Bottom tension; Catenary theory; Minimum bending radius (MBR); S-lay cable installation analysis; Submarine cable; Touch down point (TDP)